Modern Aspects of the Use of Virtopsy in Forensic Examination (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Of course, traditional, or invasive, autopsy throughout the world still remains the only way to scientifically monitor the correctness of the diagnosis and establish the cause of death and is the “gold standard” for post-mortem diagnosis. However, computed tomography (CT) and magnetic resonance imaging (MRI) have long become an integral and important part of the forensic medical examination of living persons, when expert conclusions are based on the opinions of radiologists and data from radiation diagnostic methods [7]. Virtopsy is a technique for post-mortem examination of the body, combining a classical pathological or forensic autopsy with the preliminary use of CT and/or MRI examination of the whole body without the use of contrast agents [5, 6]. The literature review examines questions about modern aspects of the use of virtopsy in forensic medicine.